CARACTERIZACIÓN DE LOS RIESGOS PSICOSOCIALES LABORALES EN TUNGURAHUA (ECUADOR): UNA REVISIÓN - Moya Núñez, Christopher Leonel; Larzabal Fernandez, Aitor; Shugulí Zambrano, Catherine Nataly; Ramos Noboa, María Isabel; Hong Hong, Adan Eduardo (Revista Ecos de la Academia, 2022)
Psycho-social risks at work are becoming significantly important in recent years. There is an increasing number of studies about psycho-social risks developing at present, including more variables. This paper is a review of scientific works about psycho-social risks at work in the province of Tungurahua (Ecuador). To this end, a documentary research based on secondary data is conducted by analysing recent research about Psycho-social risks at work. The findings show that the most concurrent risks are involvement, supervision, and workload. Furthermore, there are differences between   psycho-social risks in production and services companies.   Even though there are several studies related to Psycho-social risks at work such as performance, absenteeism, occupational diseases, and work satisfaction; all come to the conclusion that the greater the social risk at work, the lower the levels of performance and satisfaction, in addition to increasing absenteeism and occupational diseases.
Keywords: Tungurahua; Ecuador; Review; Risks al work; Psycho-social risks